2022
DOI: 10.1088/1402-4896/ac46f2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed magnetic behavior in gadolinium and ruthenium co-doped nickel oxide nanoparticles

Abstract: Pure and different concentrations from (Gd, Ru) co-doped NiO nanoparticles, capped with Polyvinylpyrrolidone (PVP), were fabricated by the co-precipitation method. The nanoparticles were characterized by different techniques. The Rietveld refinements of X-Ray Diffraction (XRD) patterns confirmed the formation of the pure face-centered-cubic NiO phase. The X-ray Photo-induced Spectroscopy (XPS) assured the trivalent oxidation state of the doped ions Gd3+ and Ru3+ and unveiled the multiple oxidation states of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…In the second order phonon mode, the 2TO mode appears and the LO+TO mode disappears in the codoped samples. Similar appearance of the 2TO mode was observed in Raman spectra of (Gd, Ru) codoped NiO nanoparticles studied previously [13]. Also, a shifting in the 2LO mode can be noticed.…”
Section: Raman Spectroscopysupporting
confidence: 87%
See 3 more Smart Citations
“…In the second order phonon mode, the 2TO mode appears and the LO+TO mode disappears in the codoped samples. Similar appearance of the 2TO mode was observed in Raman spectra of (Gd, Ru) codoped NiO nanoparticles studied previously [13]. Also, a shifting in the 2LO mode can be noticed.…”
Section: Raman Spectroscopysupporting
confidence: 87%
“…It's also reported that the main line, located at about 854 eV, arises from local screening effect, while its shoulder, located at about 856 eV, arises from non-local screening effect. The main peak undergoes a slight positive shift of ∼ 0.6 eV for x = 0.02 and ∼ 0.3 eV for x = 0.08, confirming the electronic interaction between the dopants with the Ni and is ascribed to the slight difference between their electronegativity [13]. The remaining satellite peaks appear as a result of the shake-up process due to the interaction of the photo-emitted 2p electrons with electrons in the d shell [44].…”
Section: Transmission Electron Microscopementioning
confidence: 71%
See 2 more Smart Citations
“…Hence, the reduction of the magnetocrystalline anisotropy with the increment of the non-magnetic Mg-dopants in the CuO lattice reduces the magnetostatic energy, which in turn reduces the coercivity [47]. The negligible retentivity and reduced coercivity for the synthesized Cu 1-x Mg x O nanoparticles render them magnetically clean materials recommended for data storage applications [47,48].…”
Section: Vibrating Sample Magnetometry (Vsm)mentioning
confidence: 99%